A study of the effect of traditional values and conservation of natural resources in Nigeria - Agbofuodoh Ezekiel; Onuoha Elizabeth; Arugbeni Micheal (African Journal of Environmental Economics and Management, 2018)
The role of traditional beliefs systems in the conservation of natural resources in some selected communities in Delta State, Nigeria, have been studied. Methodology of study involves the use of personal interview, literature review, group discussion, and site visitation carried out by the authors between April 2011 and March 2012. Findings show that traditional natural resources management in the selected communities are classified into the following categories: protection of particular ecosystems or habitats (such as sacred groves and sacred rivers/pond); and protection of particular animals or plant species (such as totem and tabooed species). The practices concerned relate to trees, forests, wildlife and marine organisms. The environmental wisdom and ethics expressed through these religious beliefs are very useful tools in natural resource management. Using the classification of the International Union of Conservation of Nature (IUCN), the plants and animals species in the study scared groves and forest can be described as an environment with widespread and abundant taxonomy and are not at risk or endangered.